Dynamic pathways to academic engagement in university students: a mixed-methods study on growth mindset, grit, and academic self-efficacy with ecological momentary assessment - Liang, Haizhen; Wu, Shimin (Frontiers in Psychology, 2025)
IntroductionThis mixed-methods study investigated the predictive influence of growth mindset, academic grit, and academic self-efficacy on the academic engagement of undergraduate students in mainland China. A key ancillary goal was to explore the real-time dynamics and psychological mechanisms underpinning these relationships.MethodsWe surveyed 593 students from three diverse Chinese universities to assess the core constructs. The quantitative data were analyzed using Structural Equation Modeling (SEM). To provide qualitative depth, we conducted focus group interviews (n = 3 groups) and collected Ecological Momentary Assessment (EMA) diaries from a subset of 30 participants over 14 days.ResultsThe SEM analysis showed that both growth mindset and academic grit positively predicted academic self-efficacy and engagement. Importantly, academic self-efficacy was found to partially mediate these relationships. Qualitative findings corroborated the model, revealing three key themes: (a) embracing challenges as learning opportunities, (b) self-efficacy as a cornerstone for proactive engagement, and (c) the role of cultural factors in shaping motivation. The EMA diaries provided granular, in-situ insights, illuminating how momentary perceptions of competence directly trigger or inhibit active academic involvement.DiscussionThis study underscores the importance of fostering growth mindset, grit, and especially self-efficacy to enhance academic engagement among Chinese undergraduates. The findings highlight the value of a mixed-methods approach in developing a dynamic, culturally-grounded understanding of student motivation and point toward implications for creating culturally sensitive and moment-aware educational interventions.